In vitro assays reveal inherently insecticide-tolerant termite symbionts - Blanton, Alison G.; Perkins, Samontriona; Peterson, Brittany F. (Frontiers in Physiology, 2023)
Termite symbionts are well known for conferring a myriad of benefits to their hosts. Bacterial symbionts are repeatedly associated with increased fitness, nutritional supplementation, pathogen protection, and proper development across insect taxa. In addition, several recent studies link bacterial symbionts to reduced insecticide efficacy. This has important implications both in pest control management and environmental bioremediation efforts. Insects’ guts may be a valuable resource for microbes with broad application given their unique niches and metabolic diversity. Though insecticide resistance in termites is considered unlikely due to their life history, the close association of termites with a multitude of bacteria raises the question: is there potential for symbiont-mediated pesticide tolerance in termites? We identified a candidate that could grow in minimal medium containing formulated pesticide. This bacterial isolate was then subjected to continuous culture and subsequently demonstrated improved performance in the presence of pesticide. Isolates subjected to continuous culture were then grown at a range of concentrations from 1-10X the formulation rate. After constant exposure for several generations, isolates grew significantly better. Here we demonstrate that naïve insect hosts can harbor symbionts with inherent insecticide tolerance capable of rapid adaptation to increasing insecticide concentrations overtime. This has broad implications for both pest control and environmental cleanup of residual pesticides.